Gerichtet erstarrte Mo‐Zr‐B‐Legierungen: Directionally solidified Mo‐Zr‐B alloys. Issue 11 (5th December 2017) - Bolbut, V.; Bogomol, I.; Bauer, C.; Krüger, M.
Translation abstract: Two high temperature alloys, namely Mo‐13Zr‐25.9B and Mo‐17.4Zr‐34.8B (in at. %), which were specified as eutectic compositions according to the literature were produced with a zone melting (ZM) method [1,  2]. Investigations with a scanning electron microscope demonstrated that the microstructures of both alloys are not completely eutectic. The alloy Mo‐13Zr‐25.9B shows well‐aligned arrangements of their microstructural constituents along the crystallization direction. X‐ray diffraction analysis revealed the phases molybdenum solid solution and zirconium monoboride (ZrB) in each alloy and, additionally, in alloy Mo‐13Zr‐25.9B the phases Mo2 Zr and dimolybdenum boride (Mo2 B) and in alloy Mo‐17.4Zr‐34.8B the phase zirconium diboride (ZrB2 ). Moreover, the microhardness of the individual phases was measured. The fracture toughness of both materials was determined using the SEVNB method according to DIN EN ISO 23146. Finally, the creep resistance of the alloys was tested at 1100 °C under compressive loading and compared with other molybdenum alloys and a single‐crystalline nickel based superalloy.